A Diplomatic Language. John Quincy Adams, the War of 1812, and the Origins of the Monroe Doctrine (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The document of the Monroe Doctrine, written by Secretary of State John Quincy Adams, was marked by a diplomatic language. Its essence is expressed in three key passages: separate spheres of influence for the Americas and Europe, non-colonization, and non-intervention. Originally George Canning, British Foreign Secretary, had the idea to issue a joint declaration forbidding future colonization in the Americas, but John Quincy Adams was strongly against it, remembering the war of 1812, and fearing that a bilateral declaration would limit the American western expansion. President Monroe agreed with Adams and issued a unilateral declaration. Behind this choice was not only the fear of the British, but also the rivalry with Spain and Russia for the northwestern territories, and the navigation in the Pacif Ocean to connect US commerce with China.
Keywords: Monroe, James, 1817-1825; Adams, John Quincy, 1767-1848; Monroe Doctrine; United States; Western Worlds